Normal emmetropization in infants with spectacle correction for hyperopia. - Atkinson, J; Anker, S; Bobier, W; Braddick, O; Durden, K; Nardini, M; Watson, P (2000)
PURPOSE: The development of emmetropic refraction is known to be under visual control. Does partial spectacle correction of infants' refractive errors, which has been shown to have beneficial effects in reducing strabismus and amblyopia, impede emmetropization? The purpose of the present study was to perform the first longitudinal controlled trial to investigate this question in human subjects. METHODS: Children identified as having significant hyperopia in a population screening program at age 8 to 9 months were assigned to treated (partial spectacle correction) or untreated groups. A control group of infants with no significant refractive errors at screening was also recruited. Measurements of retinoscopic refraction under cycloplegia were taken at 4- to 6-month intervals up to the age of 36 months, and changes in refraction of 148 subjects were analyzed longitudinally. RESULTS: Refractive error decreased toward low hyperopic values between 9 and 36 months in both hyperopic groups. By 36 months, this reduction of hyperopia showed no overall difference between children who were treated with partial spectacle correction and those who were not. Despite the improvement, both hyperopic groups' mean refractive error at 36 months remained higher than that of the control group. When infants in all three groups were considered together, the rate of reduction of refractive error was, on average, a linear function of the initial level of hyperopia. CONCLUSIONS: The benefits of spectacle correction for infants with hyperopia can be achieved without impairing the normal developmental regulation of refraction.